PolarX Cryoballoon metrics predicting successful pulmonary vein isolation: targets for ablation of atrial fibrillation . Issue 9 (23rd June 2022) - Honarbakhsh, Shohreh; Earley, Mark J; Martin, Claire A; Creta, Antonio; Sohaib, Afzal; Ang, Richard; Butcher, Charles; Waddingham, Peter H; Dhinoja, Mehul; Lim, Wei; Srinivasan, Neil T; Providencia, Rui; et al.
Abstract: Aim: Evaluate the novel PolarX Cryoballoon in atrial fibrillation (AF) catheter ablation through a propensity-matched comparison with the Arctic Front Advance (AFA). The aim was also to identify cryoablation metrics that are predictive of successful pulmonary vein isolation (PVI) with the PolarX Cryoballoon. Methods and results: This prospective multi-centre study included patients that underwent cryoablation for AF. All patients underwent PVI with reconnection assessed after a 30-min waiting period and adenosine. Safety, efficacy, and cryoablation metrics were compared between PolarX and a propensity-matched AFA cohort. Seventy patients were included with 278 veins treated. In total, 359 cryoablations were performed (1.3 ± 0.6 per vein) to achieve initial PVI with 205 (73.7%) veins isolating with a single cryoablation. Independent predictors for achieving initial PVI included temperature at 30 s [odds ratio (OR) 1.26; P  = 0.003] and time to reach −40°C (OR 1.88; P  < 0.001) with an optimal cut-off of ≤−38.5°C at 30 s [area under the curve (AUC) 0.79; P  < 0.001] and ≤−40°C at ≤32.5 s (AUC 0.77; P  < 0.001), respectively. Of the 278 veins, 46 (16.5%) veins showed acute reconnection. Temperature at 30 s (≤−39.5°C, OR 1.24; P  = 0.002), nadir temperature (≤−53.5°C, OR 1.35; P  = 0.003), and time to isolation (≤38.0 s, OR 1.18; P  = 0.009) were independent predictors of sustained PVI. Combining two of these three targets was associated with reconnection in only 2–5% of PVs. Efficacy and safety of the PolarX Cryoballoon were comparable to AFA Cryoballoon, however, cryoablation metrics were significantly different. Conclusions: The PolarX Cryoballoon has a different cryoablation profile to AFA Cryoballoon. Prospective testing of these proposed targets in large outcomes studies is required.